Pro-ecological activities of Slovak hotels in the opinion of their employees and consumers - Jarossová, Malgorzata A.; Knošková, Ľubica (Działania środowiskowe słowackich hoteli w opinii ich pracowników i konsumentów, 2018)
The aim of the research was to identify pro-ecological activities of Slovak hotels in the opinion of their employees and consumers. Two questionnaires were created, one was sent to 400 hotels and the other one to 105 respondents. The most common pro-ecological activities introduced by hotels were: energy saving bulbs, energy efficient appliances, waste separation and recycling, and light motion sensors. In terms of packaging of the hotel cosmetics, half of the hotels used disposable mini-packs, and the other half dispensers for soap and shampoo. Over half of hotels did not offer meals prepared from organic foods in their hotel restaurant. Only two hotels rewarded their clients who care for the environment. One hotel offered discounts on accommodation and the second one offered a higher number of points on the loyalty card. 42.1% hotels had plans related to environmental protection (e.g. expand waste sorting, recycle PET bottles, and increase the share of segregated waste)
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2018, Nr 3 (30), s. 20-30
Keywords: pro-ecological activities; Slovak hotels; customers; workers; działania proekologiczne; hotelarstwo; słowackie hotele; konsumenci; pracownicy